Experimental and computational (DFT) study of a binary system of triethanolamine and ethanol at temperatures from 293.15 to 323.15 K under 101.3 kPa - Muzhaqi, Evis; Kavakli, Aycan Altun; Sara, Osman Nuri; Fellah, M. Ferdi (Academic Press Ltd- Elsevier Science Ltd, 2025)
In this study, the density and viscosity of binary mixtures of triethanolamine (TEA) and ethanol were measured over the entire composition range at temperatures of 293.15 and 323.15 K under a pressure of 101.3 kPa. Correlations were obtained expressing density and viscosity values as a function of temperature. Excess molar volume (VE) and viscosity deviation (Delta eta) were calculated from the measured values. These properties were further fitted to the Redlich-Kister polynomial equation. Thermodynamic parameters such as partial molar volumes, apparent molar volumes, coefficients of thermal expansion, and excess Gibbs free energy of activation for viscous flow were also determined. Moreover, activation enthalpy and entropy values for viscous flow were evaluated. The experimental results and the Density Functional Theory (DFT) calculations were used to discuss the molecular interactions for binary mixtures of TEA and ethanol. Negative values of VE and Delta eta were observed across all studied temperatures and compositions, indicating strong specific interactions between TEA and ethanol molecules. There is a distinct difference in the temperature dependence of VE and Delta eta. As the temperature increases, the VE values become increasingly negative, while the Delta eta values decrease. Both experimental results and Density Functional Theory (DFT) calculations confirm the presence of intermolecular hydrogen bonding in the binary mixtures. Furthermore, FTIR spectroscopy suggests the possible presence of intermolecular interactions between the components.
Keywords: Density; Viscosity; Binary mixtures; Triethanolamine; Ethanol; Density functional theory (DFT)